Obama and Kenya : Contested Histories and the Politics of Belonging - Carotenuto, Matthew; Carotenuto, Matthew; Luongo, Katherine 1975- (Book collections on Project MUSE., 2016)
Part I. Obama and Kenya -- Discovering Obama in Kenya -- Representations of Kenya: myth and reality -- The Obama family: ethnicity and the politics of belonging in Kenya -- Part II. Contested histories and the politics of belonging -- The politics of condemnation: the American right's reactions to Obama's roots in Kenya -- The politics of celebration: ethnic grandeur and Obama's heroic embrace -- Political violence and history at the ballot box -- Obama for Africa or Africans for Obama? -- Epilogue: Tuko Pamoja: we are together.